Nurturing Creativity in the Classroom - Beghetto, Ronald A.; Kaufman, James C. (Cambridge Cambridge University Press, 2012)
"Nurturing Creativity in the Classroom is a groundbreaking collection of essays by leading scholars, who examine and respond to the tension that many educators face in valuing student creativity but believing that they cannot support it given the curricular constraints of the classroom. Is it possible for teachers to nurture creative development and expression without drifting into curricular chaos? Do curricular constraints necessarily lead to choosing conformity over creativity? This book combines the perspectives of top educators and psychologists to generate practical advice for considering and addressing the challenges of supporting creativity within the classroom. It is unique in its balance of practical recommendations for nurturing creativity and thoughtful appreciation of curricular constraints. This approach helps ensure that the insights and advice found in this collection will take root in educators' practice, rather than being construed as yet another demand placed on their overflowing plate of responsibilities"--Provided by publisher.
Machine generated contents note: 1. How to discourage creative thinking in the classroom Raymond S. Nickerson -- 2. Teaching for creativity in an era of content standards and accountability John Baer and Tracey Garrett -- 3. Developing creative productivity in young people through the pursuit of ideal acts of learning Joseph S. Renzulli and Catharina F. de Wet -- 4. Creativity: a look outside the box in classrooms Alexinia Young Baldwin -- 5. Using constraints to develop creativity in the classroom Patricia D. Stokes -- 6. Infusing creative and critical thinking into the curriculum together Elizabeth Fairweather and Bonnie Cramond -- 7. The five core attitudes, seven I's, and general concepts of the creative process Jane Piirto -- 8. Learning for creativity R. Keith Sawyer -- 9. Broadening conceptions of creativity in the classroom Ronald A. Beghetto and James C. Kaufman -- 10. Everyday creativity in the classroom: a trip through time with seven suggestions Ruth Richards -- 11. Education based on a parsimonious theory of creativity Mark A. Runco -- 12. Roads not taken, new roads to take: looking for creativity in the classroom Thomas Skiba, Mei Tan, Robert J. Sternberg and Elena L. Grigorenko -- 13. Creativity in mathematics teaching: a Chinese perspective Weihua Niu and Zheng Zhou -- 14. Possibility thinking and wise creativity: educational futures in England Anna Craft -- 15. When intensity goes to school: overexcitabilities, creativity, and the gifted child Susan Daniels and Michael M. Piechowski -- 16. Intrinsic motivation and creativity in the classroom: have we come full circle? Beth A. Hennessey -- 17. Attitude change as the precursor to creativity enhancement Jonathan A. Plucker and Gayle T. Dow -- 18. Creativity in college classrooms Diane F. Halpern; 19. Teaching for creativity Robert J. Sternberg -- 20. Creativity in the classroom coda: 20 key points and other insights James C. Kaufman and Ronald A. Beghetto.
Includes bibliographical references and index.
Also issued in print format.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Creative thinking; Creative ability; Electronic book